International Distribution as Communication Tool. What Builds Experience and Value Creation in Luxury Retail Setting? - Tisovski, Marija (2012)
The thesis argues that the distribution formats can be significant strategic communication and differentiation tools for luxury brand and that the intangible determinants within the space can provide balancing link between company trying to manage its brand expression and consumers search for the meaningful experiences. The dissertation uses a luxury retail setting, as the highest in distribution hierarchy to analyze these relations. This ensures a level of diversification from mass retail approach. In addition, this brings back to the store as source of value creation and experiences that one should expect from a luxury brand. The aim: To explore conceptually the nature of value creation and how the relationship gets between a retailer and customer translated and communicated by a means of store, also to identify the key determinants for the value creation within the formats while looking at which levels it brings to ability to co - create the experiential value with consumer. Method: The two primary methods used are: in-depth, semi-structured interview with professionals or key informants and field notes in ethnographic context with a sample of 52 international marketing students. The secondary data collection draws upon extensive, relevant and significant academic literature review including books, professional journals, online resources, etc. Findings: The work identified two value drivers: Symbolic Desire and Exclusive Excitement. Excitement and Desire were found to be the main emotions to trigger the consumer within the luxury setting and to translate a product into service or experience of a kind. Second, research identified the two experiential prospects of: Become and Belong. These show all the way the interaction builds and develops to immerse the customers in a branded world and experiences. As a result the thesis suggests two new approaches; Experiential Value Co-Creation and In - Store Typology.